2020
DOI: 10.4149/neo_2020_190815n768
|View full text |Cite
|
Sign up to set email alerts
|

Presence and prevalence of UV related genetic mutations in uveal melanoma: similarities with cutaneous melanoma

Abstract: Ultraviolet (UV) radiation is an accepted etiological factor in cutaneous melanoma (CM), however its role in Uveal Melanoma (UM) is controversial. Partly as a consequence, CM and UM are often considered to be separate conditions, and advances in the treatment of CM have not led to joint clinical trials or parallel improvements in survival of UM. This study hypothesized that a subset of UM tumors display evidence of genetic changes consistent with UV-related damage similar to that shown in CM. Analysis of the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 77 publications
1
16
1
1
Order By: Relevance
“…Aberrant BRAF -driven MAPK pathway activity is the dominant oncogenic driver in CMs [ 74 ] and is a mutation considered to be associated with UVR damage [ 75 ]. This same BRAF mutation has sometimes been observed in as high as 40% of UM samples including those arising from the choroid [ 6 , 76 , 77 ]. On the other hand, 80–96% of UMs possess GNAQ or GNA11 mutations in a mutually exclusive fashion [ 78 , 79 , 80 , 81 ], while this occurs in CM approximately 20% of the time [ 82 ].…”
Section: Molecular Changes In Um In the Context Of Uvr Influencementioning
confidence: 81%
See 3 more Smart Citations
“…Aberrant BRAF -driven MAPK pathway activity is the dominant oncogenic driver in CMs [ 74 ] and is a mutation considered to be associated with UVR damage [ 75 ]. This same BRAF mutation has sometimes been observed in as high as 40% of UM samples including those arising from the choroid [ 6 , 76 , 77 ]. On the other hand, 80–96% of UMs possess GNAQ or GNA11 mutations in a mutually exclusive fashion [ 78 , 79 , 80 , 81 ], while this occurs in CM approximately 20% of the time [ 82 ].…”
Section: Molecular Changes In Um In the Context Of Uvr Influencementioning
confidence: 81%
“…The C to T changes seen in ~35% of the 12 UMs investigated were conversely not enriched at the 3′ position of pyrimidine dimers and therefore UVR was not thought to be involved [ 71 ]. Meanwhile, Goh et al compared over 1000 UM mutations and over 12,000 CM samples and found that the proportion of samples with C to T substitutions was higher in UM (17.0%) than CM (13.1%), suggesting a substantial number of UMs are related to UVR damage [ 6 ]. A further 103 whole-genome sequencing analyses found that a significant subset of UM characterised by UVR-damage mutations was restricted to those originating from the iris [ 7 ], the most anterior structure of the uveal tract and therefore with the greatest exposure to UVR.…”
Section: Molecular Changes In Um In the Context Of Uvr Influencementioning
confidence: 99%
See 2 more Smart Citations
“…UV radiation may damage DNA in different ways, such as by creating the main promutagenic DNA adduct cyclobutene pyrimide dimer or through the formation of reactive oxygen species (ROS) [ 87 , 88 ]. In a recent study, the C > T substitute in DNA (associated with UV light) was even higher in UM than in cutaneous melanoma [ 44 ]. Because the iris is directly exposed to UV light, UV light may especially play an important role in the development of iris melanoma.…”
Section: Iris Colourmentioning
confidence: 99%